2022
DOI: 10.1093/conphys/coac001
|View full text |Cite
|
Sign up to set email alerts
|

Complex tourism and season interactions contribute to disparate physiologies in an endangered rock iguana

Abstract: To promote survival and fitness, organisms use a suite of physiological systems to respond to both predictable and unpredictable changes in the environment. These physiological responses are also influenced by changes in life history state. The continued activation of physiological systems stemming from persistent environmental perturbations enable animals to cope with these challenges but may over time lead to significant effects on the health of wildlife. In the present study, we tested how varying environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 87 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, glucose may be important in helping coqui at high elevations meet energetic demands under suboptimal temperatures. However, glucose levels respond rapidly to environmental changes such as acute stress (French et al, 2022; Gangloff et al, 2017; Kelley et al, 2021; Romero & Beattie, 2022), and previous work has demonstrated that stress may mask inherent glucose differences among populations (Hudson, Lidgard, et al, 2020). In support of this idea, previous research by Marchetti et al (2023) found a strong positive relationship between elevation and glucose in coqui, but also that stress immediately after capture could obscure these results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glucose may be important in helping coqui at high elevations meet energetic demands under suboptimal temperatures. However, glucose levels respond rapidly to environmental changes such as acute stress (French et al, 2022; Gangloff et al, 2017; Kelley et al, 2021; Romero & Beattie, 2022), and previous work has demonstrated that stress may mask inherent glucose differences among populations (Hudson, Lidgard, et al, 2020). In support of this idea, previous research by Marchetti et al (2023) found a strong positive relationship between elevation and glucose in coqui, but also that stress immediately after capture could obscure these results.…”
Section: Discussionmentioning
confidence: 99%
“…Brief elevations in GCs following a perturbation are typically beneficial and help to restore homeostasis; however, repeated or prolonged elevations can lead to wear and tear on the organism and pathological effects [13]. GCs have been used to investigate the impacts of anthropogenic disturbance and changes in habitat quality in mammals [14,15], birds [16][17][18][19], reptiles [20][21][22], amphibians [23][24][25][26] and fish [27][28][29], and they have been linked to changes in demography (reviewed in [6]).…”
Section: Introductionmentioning
confidence: 99%